V2G auxiliary frequency regulation control strategy based on state-of-charge change and user requirements - Yingjun Guo; Jiongming Xing; Qingming Zheng; Shuangqian Di; Zhe Shi; Hexu Sun (Results in Engineering)
Large-scale grid-connected electric vehicles (EVs) can act as distributed energy storage units to provide frequency regulation (FR) services. Current EV frequency control relies mainly on grid frequency deviation and user charging profiles but ignores dynamic changes in state of charge (SOC) and regulation characteristics, leading to inefficient FR and unmet charging demands. To address this, this paper proposes a dynamic SOC-based adjustment of unit power and FR capability coefficients, enabling coordinated grid frequency stabilization while meeting charging requirements. Simulations verify the strategy: When SOC is within the optimal FR range, it increases FR output by 2.5 kW over conventional methods. Near full charge or discharge limits, FR power drops near zero, allowing safe exit from regulation. For example, with a 3-hour charging time, the FR participation factor reaches 0.7, yielding 3 kW output. The results show enhanced FR capability while flexibly balancing grid frequency, SOC levels, and user charging needs for optimized control.